Hands-on childcare garden intervention: A randomized controlled trial to assess effects on fruit and vegetable identification, liking, and consumption among children aged 3–5 years in North Carolina - Cosco, Nilda G.; Wells, Nancy M.; Zhang, Daowen; Goodell, L. Suzanne; Monsur, Muntazar; Xu, Tong; Moore, Robin C. (Frontiers in Psychology, 2022)
Gardening at childcare centers may have a potent influence on young children’s learning about fruits and vegetables and their development of healthy dietary behaviors. This randomized controlled trial examined the effect of a garden intervention on fruit and vegetable (FV) identification, FV liking, and FV consumption among 3–5-year-old children enrolled in childcare centers in Wake County, North Carolina. Eligible childcare centers (serving primarily low-income families) were randomly selected and then randomly assigned to one of three groups: 1) intervention; 2) waitlist-control that served as a control in year 1 and received the intervention in year 2; or 3) no-intervention control. From the 15 participating childcare centers, 250 children aged 3-5 years were consented by their parents or guardians to participate. The intervention comprised six standardized, raised, mulched garden beds, planted with warm-season annual vegetables and fruits and perennial fruits. A Gardening Activity Guide describing 12 age-appropriate, sequential gardening activities was distributed for teachers to lead hands-on gardening activities during the growing season. Data were gathered at baseline (Spring 2018) and at three follow-up waves (Fall 2018, Spring 2019, Fall 2019). FV identification and liking were measured using an age-appropriate tablet-enabled protocol. FV consumption was measured by weighing each child’s fruit and vegetable snack tray before and after a tasting session. Compared to children receiving no intervention, children who received the gardening intervention showed a greater increase in accurate identification of both fruits and vegetables as well as consumption of both fruit and vegetables during the tasting sessions. Consistent with prior research, the effects of fruit consumption were greater than for vegetable consumption. There was no significant effect of the gardening intervention on children’s FV liking. Gardening interventions implemented early in life foster learning about FV and promote healthy eating. Early exposure to gardening may yield a return on investment throughout the life course—impacting healthy diet and associated health outcomes, which is particularly important within under-resourced communities where children’s health is challenged by a host of risk factors. Clinical Trials Registration #NCT04864574 (clinicaltrials.gov).